The Impact of social networking site usage on Academic Performance: An analytical study among college students (Journal of Advances and Scholarly Researches in Allied Education, 2024)
We live in a global community now. The Internet creates a network in which all users are linked to one another. "The new electronic independence re-creates the world in the image of a global village," communication theorist Marshall Mc Luhan said. Internet connectivity is fundamental to this digital autonomy. As a result of its worldwide dissemination of information, it makes us all citizens of the world by illuminating the lives of countless individuals. Yet, students are often led astray by the many social media sites, which divert their attention away from studying and onto other activities, rather than utilising them to further their education. The purpose of the research is to determine the influence of social media and to evaluate the negative impacts on their academic achievement. In addition, it makes an effort to shed light on the several causes of their low academic performance as a result of social media addiction. Finding a happy medium between productive social media use and academic responsibilities is another goal of the research. It aims to provide advice on how to handle the current social media trend while still meeting academic obligations.